Disseminated intravascular coagulation complicating mild or asymptomatic maternal COVID-19AJOG Global Reports at a Glance - Jeanette Carpenter, MD; C. Andrew Combs, MD, PhD; Bronwen Kahn, MD; Kimberly Maurel, MSN, CNS, RN; Reese Clark, MD (Elsevier, 2022)
BACKGROUND: Hypercoagulability frequently complicates moderate or severe COVID-19 and can result in venous thromboembolism, arterial thrombosis, or microvascular thrombosis. Disseminated intravascular coagulation, however, is uncommon. OBJECTIVE: We sought to describe the clinical presentation and outcome in a series of pregnant patients with mild or asymptomatic COVID-19 who had disseminated intravascular coagulation. STUDY DESIGN: This was a retrospective case series. Cases were solicited via e-mails targeted to obstetrical providers in the Mednax National Medical Group and a restricted maternal-fetal medicine Facebook page. Inclusion criteria were: hospital admission during pregnancy, positive test for SARS-CoV-2 within 2 weeks of admission, and maternal disseminated intravascular coagulation defined as ≥2 of the following: platelet count ≤100,000 per mm3, fibrinogen ≤200 mg/dL, and prothrombin time ≥3 seconds above the upper normal limit. Exclusion criteria were severe COVID-19 requiring ventilation within an hour of diagnosis of coagulopathy or use of anticoagulants at the time of diagnosis. Maternal and newborn records were abstracted and summarized with descriptive statistics. RESULTS: Inclusion criteria were met in 19 cases from October 2020 through December 2021. Of these, 18 had not received any COVID-19 vaccine, and 1 had unknown vaccination status. Median gestational age on hospital admission was 30 weeks (interquartile range, 29-34 weeks). The main presenting symptom or sign was decreased fetal movement (56%) or nonreassuring fetal heart rate pattern (16%). COVID-19 was asymptomatic in 79% of cases. Two of the 3 defining coagulation abnormalities were found in 89% of cases and all 3 in the remaining 11%. Aspartate aminotransferase was elevated in all cases and ≥2 times the upper normal limit in 69%. Only 2 cases (11%) had signs of preeclampsia other than thrombocytopenia or transaminase elevation. Delivery was performed on the day of admission in 74% and on the next day in the remaining 26%, most often by cesarean delivery (68%) under general anesthesia (62%) because of nonreassuring fetal heart rate pattern (63%). Postpartum hemorrhage occurred in 47% of cases. Blood product transfusions were given in 95% of cases, including cryoprecipitate (89% of cases), fresh/frozen plasma (79%), platelets (68%), and red cells (63%). Placental histopathology was abnormal in 82%, with common findings being histiocytic intervillositis, perivillous fibrin deposition, and infarcts or necrosis. Among the 18 singleton pregnancies and 1 twin pregnancy, there were 13 live newborns (65%) and 7 stillbirths (35%). Among liveborn neonates, 5-minute Apgar score was ≤5 in 54%, and among cases with umbilical cord blood gases, pH ≤7.1 was found in 78% and base deficit ≥10 mEq/L in 75%. Positive COVID-19 tests were found in 62% of liveborn infants. CONCLUSION: Clinicians should be alert to the possibility of disseminated intravascular coagulation when a COVID-19 patient complains of decreased fetal movement in the early third trimester. If time allows, we recommend evaluation of coagulation studies and ordering of blood products for massive transfusion protocols before cesarean delivery if fetal tracing is nonreassuring.